Association between Functional Status of Patients and Cognitive Impairment in End Stage Renal Disease - Asma Arman; Mahjabeen Yaseen; Tahir Ansari; Natasha Billia; Mehwish Arif Butt (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2022)
ABSTRACT